Interactive effects of depth and differential irrigation on soil microbiome composition and functioning - Naylor, Dan; Naasko, Katherine; Smith, Montana; Couvillion, Sneha; Nicora, Carrie; Trejo, Jesse; Fransen, Steven; Danczak, Robert; McClure, Ryan; Hofmockel, Kirsten S.; Jansson, Janet K. (Frontiers in Microbiomes, 2023)
Two factors that are well-known to influence soil microbiomes include the depth of the soil as well as the level of moisture. Previous works have demonstrated that climate change will increase the incidence of drought in soils, but it is unknown how fluctuations in moisture availability affect soil microbiome composition and functioning down the depth profile. Here, we investigated soil and wheatgrass rhizosphere microbiomes in a common field setting under four different irrigation regimes and three depths. We demonstrated that there is a significant interactive effect, where fluctuations in soil moisture more strongly influence soil microbiomes at the surface layer than in deeper layers, including for soil community composition, diversity, and for functional profiles. Meanwhile, in rhizosphere communities the influence of irrigation was similar across the different depths, although there were slight discrepancies between the two cultivars of wheatgrass used. The lessened response of deeper soil microbiomes to changes in irrigation may be due to higher incidence of slow-growing, stress-resistant microbes.